Decision of Linked with Narcotics Convicted in Act No. 35 Of 2009 in The District of Sumber Court - Heni Agustiningsih; Sri Endah Wahyuningsih (Jurnal Daulat Hukum, 2018)
Concomitant with the increasing number of criminal cases concerning criminal law talks even more into the spotlight. One criminal case whose numbers have increased is the narcotic crime. The doers are not limited to age, gender or social strata. Increasing this narcotic crime was accompanied by the use of increasingly sophisticated modus operandi so, make the legislators felt the need to establish a new law governing narcotics. Judge in deciding should consider the value of certainty, justice and the role of the judge is kemafaatan for law enforcement and justice. Article 1 (1) of Act No. 48 Of 2009 regarding Judicial Power.Keywords: Effectiveness; Criminal Law;  Narcotics.